Pengaruh Pertumbuhan Perusahaan, Leverage, Komisaris Independen, dan Modal Bersih Terhadap Kinerja Keuangan - Robby Benny Aryando; Yanuar Ramadhan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to provide empirical evidence regarding the influence of company growth, debt levels, independent commissioners, net working capital on financial performance. This research method uses quantitative research methods. The research object is food and beverage companies listed on the Indonesian stock exchange during 2020-2022. The data source in this research uses secondary data, namely data contained on the official IDX website, namely www.idx.co.id and the official website of the related company. The population used in this research is 30 food and beverage manufacturing companies listed on the Indonesian stock exchange for the 2020-2022 period. The number of samples taken was 30 companies, so the data obtained was 90 data. The research results show that company growth has a significant positive effect on the financial performance of consumer goods sub-sector manufacturing companies listed on the IDX in 2020-2022. Debt levels have a significant negative effect on the financial performance of Consumer Goods Sub-Sector Manufacturing Companies Listed on the IDX in 2020-2022. Commissioners have a significant positive influence on the financial performance of Consumer Goods Sub-Sector Manufacturing Companies Listed on the IDX in 2020-2022. Net working capital has a significant positive effect on the financial performance of Consumer Goods Sub-Sector Manufacturing Companies Listed on the IDX in 2020-2022. Simultaneously, company growth, debt levels, commissioners, dividend policy and net working capital have a significant positive effect on the financial performance of Consumer Goods Sub-Sector Manufacturing Companies Listed on the IDX in 2020-2022.